Operando spin observation elucidating performance-improvement mechanisms during operation of Ruddlesden–Popper Sn-based perovskite solar cells - Yizhou Chen; Seira Yamaguchi; Atsushi Sato; Dong Xue; Kazuhiro Marumoto (npj Flexible Electronics)
Abstract Sn-based perovskite solar cells (PSCs) have attracted attention because of their low environmental impact. Unfortunately, the readily occurring oxidation of Sn2+ inhibits further improvement of their efficiency and stability. Ruddlesden–Popper (RP) Sn-based perovskites are considered promising candidates as absorbers that improve the performance and stability of Sn-based PSCs. However, microscopic understanding of performance-enhancing mechanisms remains insufficient. For this study, electron spin resonance (ESR) spectroscopy measurements were taken of RP Sn-based PSCs with poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) hole-transport layers and (BA0.5PEA0.5)2FA3Sn4I13 perovskite layers to clarify the space-charge region formation mechanism at the PEDOT:PSS/(BA0.5PEA0.5)2FA3Sn4I13 interface. These results indicated electron-barrier formation in the (BA0.5PEA0.5)2FA3Sn4I13 layer near the PEDOT:PSS layer. Moreover, the electron barrier was found to be enhanced during device operation. The enhanced interface band bending reduces interface recombination and thereby improves the device's performance. These findings might provide important progress in practical applications of PSCs and might advance the realization of a carbon-neutral society.